2022
DOI: 10.1177/26349833221102471
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of RC beams externally strengthened with a single-layer of basalt fiber reinforced polymer sheets

Sara Kadhim,
Mustafa Özakça

Abstract: Basalt Fiber Reinforced Polymer (BFRP) is an environment friendly strengthening material that can be used in several engineering applications. In this research, an experimental program was directed to investigate the BFRP strengthening adequacy of reinforced concrete beams. Eight simple-span beams were tested under the four-point bending test and were all made from the same concrete mixture. One layer of BFRP was applied on the soffit of B1, while this layer was wrapped partially along the sides of beams B2, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…vn=fce*sinθs*bw*ws (12) where fce = 0.85βs fc , ws = min [(wt cosθs + wb sinθs), (hc cosθs + wb sinθs )] βs for bottle-shaped struts with reinforcement satisfying Section A. 3…”
Section: Equations Used To Determine the Ultimate Load Of The Deep Be...mentioning
confidence: 99%
See 2 more Smart Citations
“…vn=fce*sinθs*bw*ws (12) where fce = 0.85βs fc , ws = min [(wt cosθs + wb sinθs), (hc cosθs + wb sinθs )] βs for bottle-shaped struts with reinforcement satisfying Section A. 3…”
Section: Equations Used To Determine the Ultimate Load Of The Deep Be...mentioning
confidence: 99%
“…so, we choose this fiber trying to solve the problems which happen due to existing of openings in deep beams such as the reduction in strength of the beam, more cracks, and deflection in addition to that, openings disrupt the normal stresses flow, resulting in concentration of stress at the openings' sides and early cracking of concrete by strengthening these openings with basalt fiber reinforced polymer sheets, and also trying to solve the problem of pollution due to carbon fiber. The last searches of BFRP were about its behavior individually, as a ratio of concrete mix, BFRP bars, and as a strengthening material (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Hannibal Ólafsson et al (3) made a review on basalt fiber, the different methods of production, and tests done on it as a strengthening material for R.C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A catastrophic failure in plain concrete was observed in the loading direction and is depicted in Figure 5(a). Enhancing the strength of concrete can be achieved by the wrapping technique, but reduced ductility was observed with this technique (15,18,19,28) . This is due to brittle failure of concrete and hence transfer of load to FRP wrapped jacket.…”
Section: Compression Testmentioning
confidence: 99%
“…Wrapping of Fiber Reinforced Polymer [FRP] enhances the load-carrying capacity and deflection (14) . The effect of BFRP wrapping on the bottom and vertical side of the beam on flexural performance was studied by Sara Kadhim et.al (15) . The author reported that the ductility of BFRP-wrapped beams is less than the reference beam.…”
Section: Introductionmentioning
confidence: 99%